The Effect Of Understanding Of Government Accounting Standards And The Utilization Of Regional Financial Accounting Information Systems On The Quality Of Regional Government Financial Reports In Parepare City - Ahmad Dani (Journal AK-99, 2023)
utilization of regional financial accounting information systems on the quality of regional financial reports. This research uses quantitative research methods. Data obtained from primary data, namely through the distribution of questionnaires. Research respondents are leaders and staff who are directly involved. The questionnaire was processed using the SmartPLS 3.0 application. Based on the research results, the understanding of government accounting standards has a significant positive effect because in the process of presenting local government financial reports it must be supported by a good basis or foundation, one of which is an understanding of supporting government accounting standards. Utilization of the Regional Financial Accounting Information System has a significant effect on the quality of local government financial reports due to the increasingly rapid development of technology and information networks, if it is not utilized as well as possible, it is definitely useless and outdated. The government in response to this development is carried out so that the process can be simplified and the delivery of information is fast and accurate, data confidentiality and security can be maintained, cost efficiency in the process of managing transaction data so as to produce quality financial reports.